PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Widayati, Catur; H. Rahardjo, Thea; Febriyanti, Melly (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
This research aims to examine and analyze the influence of Transformationalleadership style, motivation and compensation on performance of employees at PT.Hanken Indonesia Cibitung. The methods used in this research is descriptive method. The object of this research is all staff office division who worked in PT. Hanken Indonesia Cibitung with a population 125 people. Sampling technique using non-probability sampling with total samples is 95 people. The approach used in this research is a Structural Equation Models (SEM) with Smart analysis tools-PLS. The results showed transformational leadership style gives a positive and significant influence on employee performance. Work motivation has no significant on employee performance.Compensation provides a positive and significant effect on performance employees. This is evidenced from the results of hypothesis testingÂ (t-test) which shows the significance value of the independent variables.